New Social Movements: “Refugees Welcome UK” - Koca, Burcu Togral (European Scientific Journal, ESJ, 2016)
This study addresses the dynamics of new social movements with a special emphasis on the “Refugees Welcome UK” in the light of the Syrian refugee crisis. Since March 2011, over four millions of people have fled civil war in Syria and sought refuge mainly in neighbouring countries, such as Turkey, Jordan, Egypt and Lebanon. However, precarious living circumstances and uncertain legal status in these countries have forced hundreds of thousands of Syrians to head for Europe in quest for a better life. The European countries, on the other hand, have adopted restrictive approaches towards Syrian refugees. Among these European countries, the UK has been the most criticized one because of its indifference to the plight of Syrian refugees. Under the leadership of David Cameron, the UK has taken a restrictive stance on accepting Syrian refugees and resisted any solution attempts at the EU level. Contrary to this anti-refugee approach at the state level, there emerged social movements in support of refugees throughout the UK. The most prominent one is the “Refugees Welcome” movement engaging in various strategies, ranging from seeking donation to raising public awareness. Building upon the insights of “New Social Movements” paradigm and using documentary analysis, this article explores the dynamics of this movement, its demands and objectives, social base, organizational structure, mobilization strategies and medium of action and social location. The article seeks to contribute both to the literature on social movements and to the current debate on refugees.